The Relationship between Nutritional Status and Dysmenorrhea Degree in Female Students of SMA Negeri 1 Surakarta - Yuniandry, Ristyadita; Lestari, Endang Dewi; Prasetyawati, Arsita Eka (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: Dysmenorrhea is young women problem. Dysmenorrhea is lower abdominal pain that is felt before or during menstruation. One factor that may lead to primary dysmenorrhea is nutritional status. This study aim is to determine the relationship between nutritional status and degree of dysmenorrhea in female students of SMA Negeri 1 Surakarta. Methods: This research is an observational analytic with cross sectional approach. This research was conducted in SMA Negeri 1 Surakarta. The population was class X female students of SMA Negeri 1 Surakarta who have experienced menstruation period at least 1 year, dysmenorrhea, not smoking, not consuming alcohol, willing to be respondent, L-MMPI scores with the answer